2016
DOI: 10.1523/eneuro.0169-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral and Contralateral Retinal Ganglion Cells Express Distinct Genes during Decussation at the Optic Chiasm

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 83 publications
6
70
1
1
Order By: Relevance
“…Several lines of evidence point to Cyclin D2 as a key regulator of cell cycle progression and neurogenesis (Glickstein et al, ; Komada, Iguchi, Takeda, Ishibashi, & Sato, ; Petros et al, ; Tsunekawa et al, ; Tsunekawa & Osumi, ). Gene profiling revealed that Cyclin D2 is differentially expressed in the mouse retina, with more cells expressing Cyclin D2 in the ventral than in the dorsal CMZ (Wang et al, ). In addition, in the absence of Cyclin D2, a reduced number of i‐ and cRGCs are found in VT retina and the ipsilateral projection is reduced, indicating that a subset of i‐ and cRGC progenitors reside in the ventral CMZ (Marcucci et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence point to Cyclin D2 as a key regulator of cell cycle progression and neurogenesis (Glickstein et al, ; Komada, Iguchi, Takeda, Ishibashi, & Sato, ; Petros et al, ; Tsunekawa et al, ; Tsunekawa & Osumi, ). Gene profiling revealed that Cyclin D2 is differentially expressed in the mouse retina, with more cells expressing Cyclin D2 in the ventral than in the dorsal CMZ (Wang et al, ). In addition, in the absence of Cyclin D2, a reduced number of i‐ and cRGCs are found in VT retina and the ipsilateral projection is reduced, indicating that a subset of i‐ and cRGC progenitors reside in the ventral CMZ (Marcucci et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the fraction of cells that exit the cell cycle by injecting EdU at E13 and determining the coincidence of EdU and Ki67 in the CMZ at E14.5, comparing Cyclin D2 −/− to Cyclin D2 +/+ littermates. Cyclin D2 is enriched in ventral CMZ and expressed at low levels in dorsal CMZ, and is absent from the neural retina, including the sectors named as peripheral neural retina in Figure a,b (Marcucci et al, ; Wang et al, ). Hence, we compared cell cycle exit in ventral and dorsal CMZ and in ventral and dorsal peripheral retina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hes5 is expressed in Ki67 + progenitor cells in the neuroblastic layer but not in the ciliary marginal zone (CMZ) which is a source of RGCs (Marcucci et al, 2016; Wang et al, 2016). Notch1 is also highly expressed in the neuroblastic layer and moderately expressed in the RGC layer.…”
Section: Resultsmentioning
confidence: 99%
“…How is proliferation and differentiation of ipsilateral RGCs which are situated in VT retina, regulated? Most recently, we have identified Cyclin D2 as a regulator of cell cycle progression and exit in VT retina during the production of Zic2 + RGCs (Marcucci et al, 2016; Wang et al, 2016). As overexpression of Hes5 in VT retina has no effect on RGC differentiation, contralateral and ipsilateral RGC differentiation may be mediated by distinct molecules and/or downstream signals of Hes5.…”
Section: Discussionmentioning
confidence: 99%